Análise do efeito do hidrogênio na resposta de tenacidade à fratura em junta soldada dissimilar - Silva, Adiana Nascimento (2018)
Dissimilar welded joints have been used extensively in the petroleum industry for some time. In the last decade, failures, many of them of catastrophic proportions, began to appear in the exploration and transportation of offshore oil, such as those that occurred in the Gulf of Mexico and in the North Sea. This fact has generated great concern in the oil sector, which is currently one of the main users of this type of joint. Several components of the offshore system employ the welding of dissimilar metals, iron-nickel, which are subjected to cathodic protection to prevent corrosion. The root cause of these failures has been associated with the presence of hydrogen from this protection system, together with the microstructure of the dissimilar interface. The central motivation of our work is the analysis of the susceptibility to the embrittlement by hydrogen, through the fracture toughness behavior, for the base metal, forged steel ASTM A182 F22, and dissimilar welded joint of steel ASTM A182 F22 - Inconel 625 - ASTM A36 steel. The weld metal, Inconel 625, was used in both buttery welding and welding, with both welds made by the conventional GMAW (Gas Metal Arc Welding) process. The hydrogenation process was carried out with a 3.5% NaCl aqueous solution, potential of -1,100 mVSCE, for 7 days at 0ºC. The influence of hydrogen was also analyzed by means of a tensile test considering also the base metal and welded joint. In the study of fracture toughness the three-point flexural test was used, and the fatigue pre-crack was located in the ZTA of ASTM A182 F22 steel, approximately 1mm from the melt line. The toughness parameter raised in this work was the Crack Tip Open Displacement (CTOD), which is recommended for weld joint studies. Microstructural analysis was performed using optical and scanning electron microscopy, using Normal Cross-Section (NCS) and LAMS (Lowangle Microsectioning) samples. Both the tensile and CTOD test results indicated that the maintenance of the mechanical properties of the forged ASTM A182 F22 steel with predominantly ductile fracture behavior be made by dimples. With respect to welded joint, with hydrogenation, susceptibility to embrittlement by hydrogen was verified, both in terms of ductility and fracture toughness. The presence of a mixed fracture mechanism, such as dimples, MVC ("cellular") and quasi-cleavage, was observed, deferring of the nonhydrogenated joint, which presented a ductile fracture mechanism. The test crack developed predominantly in the HAZ coarse grained region (Δ zone), showing no deviation from the fatigue crack, for the conditions without and with hydrogenation. Macrosegregation was evident in microstructural analyzes of the dissimilar interface. We were able to observe the presence of austenite retained in the interface of the buttering weld in the as-welded state, as well as the presence of martensite after PWHT, which, because they are hydrogen trapping microstructures, are directly related to the embrittlement process.